Circulating Neutrophils of Nonalcoholic Steatohepatitis Patients Show an Activated Phenotype and Suppress T Lymphocytes Activity. (30th June 2020) - Antonucci, Laura; Porcu, Cristiana; Timperi, Eleonora; Santini, Silvano Junior; Iannucci, Gino; Balsano, Clara
Abstract : Neutrophils or PolyMorphonuclear Neutrophils (PMNs) are key effector cells of the innate immune system and thanks to their remarkable plasticity, establish a cross talk with T cells modulating their survival and effector functions. During Nonalcoholic Steatohepatitis (NASH), the advanced form of hepatic steatosis or NAFL, PMNs infiltrate liver tissue, becoming a histological feature of NASH. Our aim was to evaluate the frequency of PMNs in NAFL and NASH patients in order to understand how they modulate the activity of circulating CD4 + and CD8 + T cells. In our cohort of patients, NASH patients displayed a higher frequency of circulating PMNs that was strongly correlated to liver enzymes, grade of steatosis, inflammation and fibrosis, the hepatocellular ballooning, and NAFLD Activity Score (NAS). Furthermore, even if ex vivo, in both groups of patients, PMNs shared the same phenotype of resting cells, after 24 hours of coculture with autologous CD4+ and CD8+ T cells, PMNs of NASH patients acquired a more active phenotype, becoming able to strongly inhibit proliferation and activation of CD4 + and CD8 + T cells. The higher ability of PMNs of NASH patients in suppressing CD4 + and CD8 + T cells, over time, might contribute in reducing the immunological defense of liver tissue against damages thus taking part in the progression of the NAFL disease toward NASH.